Pelatihan Reparasi Perahu Fiberglass bagi Nelayan Kabupaten Takalar - Zulkifli Yusuf; M. Rusydi Alwi; Ganding Sitepu; Andi Haris Muhammad; Baharuddin -; Andi Husni Sitepu; M. Iqbal Nikmatullah; Lukman Bochary; Misliah - (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
The “Karya Bersama” Fishermen Group is one of the fishermen groups in Galesong Kota Village, Galesong District, and Takalar Regency who uses fiberglass boats for fishing activities. The fiberglass boats used are very helpful for fishermen in increasing their catch. Based on field observations, it was found that several fiberglass boats belonging to partners were damaged. The damage to the fiberglass boats they use cannot be avoided due to the unclean waters of the fishing location and the large waves. They cannot do proper fiberglass boat repair independently because their knowledge and skills in fiberglass boat repair techniques are still low. This service activity aims to improve partners' knowledge and skills in fiberglass boat repair techniques. The activity was carried out in two stages, namely 1) Counseling about fiberglass material technology, types of damage to fiberglass boats and repair techniques. 2) Fiberglass boat repair training. Evaluation of the increase in participants' knowledge was carried out by means of a pre-test and post-test after counseling. Evaluation of participants' skills is carried out during hands-on training. The results of the activity showed that 90% of the 10 participants who took part in the training had good knowledge of fiberglass materials and fiberglass boat repair techniques and were able to properly repair damaged fiberglass boats.